Psychological eHealth Interventions for Patients With Cardiovascular Diseases: Systematic Review and Meta-Analysis - Su, Jing Jing; Lin, Rose; Batalik, Ladislav; Wong, Arkers Kwan Ching; Grace, Sherry L (JMIR. Journal of medical internet research, 2025)
BACKGROUND: Psychological distress is recognized as an independent risk factor for cardiovascular diseases (CVDs), contributing to increased morbidity and mortality. While eHealth is increasingly used to deliver psychological interventions, their effectiveness for patients with CVDs remains unclear. OBJECTIVE: This meta-analysis aimed to evaluate the effects of eHealth psychological interventions for patients with CVDs. METHODS: Eligible studies were retrieved from 5 databases (Embase, Medline, PubMed, CINAHL, and Cochrane Library), covering the period from database inception to December 2024. Randomized controlled trials (RCTs) investigating the effect of evidence-based psychological eHealth interventions to improve psychosocial well-being and cardiovascular outcomes for people with CVDs were included. The Cochrane Risk of Bias tool (version 2) was used to judge the methodological quality of reviewed studies. RevMan (version 5.3) was used for meta-analysis. RESULTS: A total of 12 RCTs, comprising 2319 participants from 10 countries, were included in the review. The results demonstrated significant alleviation of depressive symptoms for patients receiving psychological eHealth intervention compared to controls (number of paper included in that particular analysis, n=7; standardized mean difference=-0.30, 95% CI -0.47 to -0.14; I2=57%; P<.001). More specifically, in 6 trials where internet-based cognitive behavioral therapy was delivered, a significant alleviation of depressive symptoms was achieved (standardized mean difference=-0.39, 95% CI -0.56 to -0.21; I2=53%; P<.001). There was no significant change in anxiety or quality of life. Synthesis without meta-analysis regarding stress, adverse events, and cardiovascular events showed inconclusive findings. CONCLUSIONS: Psychological eHealth interventions, particularly internet-based cognitive behavioral therapy, can significantly reduce depressive symptoms among patients with CVDs. A multidisciplinary approach is crucial for comprehensively improving psychological and cardiovascular outcomes. Future studies should explore integrating persuasive design features into eHealth and involving mental health professionals for intervention delivery. TRIAL REGISTRATION: PROSPERO CRD42023452276; https://www.crd.york.ac.uk/PROSPERO/view/CRD42023452276.
Keywords: Telemedicine; telemedicína; deprese; randomizované kontrolované studie jako téma; Cognitive Behavioral Therapy; lidé; Randomized Controlled Trials as Topic; kardiovaskulární nemoci; Cardiovascular Diseases; Humans; kognitivně behaviorální terapie; Depression